(untitled) (Bangladesh Journal of Plant Taxonomy, 2023)
Peyssonnelia conchicola Piccone and Grunow, Gymnothamnion elegans (Schousboe) J. Ag. (reds) and Spatoglossum schroederi (Mertens) Kütz. (brown) seaweeds as new records are described and reported here in the second part of studies in the St. Martin’s Reef. This along with the eight seaweeds (with six new records) recorded and described in the first part earlier, the total taxa now are 11 (eleven). Again, all the eight samples were collected in a single day light period. Through extensive studies including sub-littoral zones of the two tiny Reefs having crystal clear water is expected to yield many seaweed species, including new ones. Bangladesh J. Plant Taxon. 30(2): 249-254, 2023 (December)